DIVERSITY in binding, regulation, and evolution revealed from high-throughput ChIP - Mitra, Sneha; Biswas, Anushua; Narlikar, Leelavati (PLOS Computational Biology, 2018)
Author summary A high-throughput chromatin immunoprecipitation (ChIP) experiment identifies genomic regions bound by a protein in vivo. Current motif-discovery approaches seek an enriched motif signature in the reported regions, which they can attribute to the protein’s binding preferences. However, Diversity models the fact that since a ChIP experiment pulls down regions participating in all complexes involving the profiled protein, the reported regions are in all likelihood, a collection of different types of protein-DNA contacts. Diversity asks a different question: what sequence component caused a specific region to be reported in a ChIP experiment? The answer, in combination with additional data such as sequence conservation, SNPs, chromatin structure, downstream gene-expression, etc. can yield insights into the diverse regulatory mechanisms at play. The added benefits of a webserver and a standalone parallel version make diversity a practical tool for discovering new biology from ChIP experiments.